Respecting truth willful ignorance in the Internet age - McIntyre, Lee C. (New York Routledge/Taylor & Francis Group, 2015)
Throughout history, humans have always indulged in certain irrationalities and held some fairly wrong-headed beliefs. But in his newest book, philosopher Lee McIntyre shows how we've now reached a watershed moment for ignorance in the modern era, due to the volume of misinformation, the speed with which it can be digitally disseminated, and the savvy exploitation of our cognitive weaknesses by those who wish to advance their ideological agendas. In Respecting Truth: Willful Ignorance in the Internet Age, McIntyre issues a call to fight back against this slide into the witless abyss. In the tradition of Galileo, the author champions the importance of using tested scientific methods for arriving at true beliefs, and shows how our future survival is dependent on a more widespread, reasonable world.
Includes bibliographical references (pages 142-144) and index.
Keywords: Irrationalism (Philosophy); Truthfulness and falsehood -- Philosophy; Self-deception -- Philosophy; Mass media -- Objectivity; Internet -- Psychological aspects